Pengaruh Karakteristik Pekerjaan, Karakteristik Organisasi Dan Karakteristik Individu Terhadap Kepuasan Kerja Pegawai Di Kantor Camat Dau Kabupaten Malang - Muamar Kadafi; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to analyze the effect of job characteristics, organizational characteristics, individual characteristics on employee job satisfaction in the District Office of Dau Malang Regency. The population of this study was all employees of the District Office of Dau Malang Regency as many as 32 people while the sample in this study amounted to 32 consumers. Data analysis uses multiple linear regression analysis.The results of this study show that the variables of work characteristics, organizational characteristics and individual characteristics have a significant influence simultaneously on the variable job satisfaction of Dau District Camat Office employees in Malang Regency. Partially the job characteristics and organizational characteristics have a significant influence on employee job satisfaction variables in the Dau District Head Office of Malang Regency. While the individual characteristics. has a partially insignificant influence on the variable of job satisfaction of employees of Dau District Head Office of Malang Regency Keywords: Job Characteristics, Organizational Characteristics, Individual Characteristics, Job Satisfaction